2000
DOI: 10.1097/00005537-200011000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Combined Radiotherapy With Planned Neck Dissection for Small Head and Neck Cancers With Advanced Cervical Metastases

Abstract: Background: We have previously described our treatment algorithm for patients with small head and neck cancers with advanced cervical metastases (stage N2 or greater). Primary radiotherapy is given to the primary site and neck, followed 6 weeks later with endoscopy and biopsy of the primary site. If biopsy of the primary site is negative by frozen section, an immediate neck dissection is performed even when no clinical residual neck disease is present. Our initial review found that 36% of patients with a compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
26
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 17 publications
6
26
0
Order By: Relevance
“…However, it remains controversial whether to perform a planned neck dissection for patients with bulky disease (N2-N3) who have a clinical complete response to chemoradiation. 3 A few studies [4][5][6][7] suggest that clinical assessment (including posttreatment imaging) after radiotherapy or chemoradiotherapy cannot ensure the absence of neck disease. Wang et al 4 found that 31% of patients had pathological positive nodes following a complete clinical response.…”
Section: Resultsmentioning
confidence: 99%
“…However, it remains controversial whether to perform a planned neck dissection for patients with bulky disease (N2-N3) who have a clinical complete response to chemoradiation. 3 A few studies [4][5][6][7] suggest that clinical assessment (including posttreatment imaging) after radiotherapy or chemoradiotherapy cannot ensure the absence of neck disease. Wang et al 4 found that 31% of patients had pathological positive nodes following a complete clinical response.…”
Section: Resultsmentioning
confidence: 99%
“…Others recommend neck dissection for all N2 and N3 diseases regardless of the response to therapy [21,22] .…”
Section: Discussionmentioning
confidence: 99%
“…Although most withhold adjuvant neck dissection after a complete response for initially small disease burden in the neck, there is an ongoing debate regarding the management of N2 or N3 disease with many institutions performing neck dissection even if achieving a complete response to radiation with or without chemotherapy. 10,12,14,15,28,[33][34][35] Neck dissection is also routinely offered to nodal levels that have achieved a PR or a ''very good PR'' to radiation with or without chemotherapy due to at least a 15% to 25% risk of containing viable metastatic disease. [35][36][37] Recently, there has been an increased interest in the use of posttreatment FDG-PET scans to help determine whether viable tumor remains in the neck and thus warrants a neck dissection.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] Although some have used the posttreatment response based on CT imaging and/or fluorodeoxyglucose positron emission tomography (FDG-PET) scan to guide further therapy, others recommend routine neck dissection for initial bulky (>4.5 or 5 cm) nodal disease based on the poor negative predictive value (NPV) of a complete response in predicting pathologic outcomes. 10,12,15 Recently, neck dissection has been shown to be associated with an increase in late morbidity compared with radiation-based therapy alone. 16 Moreover, similar neck control rates for selective neck dissection (SND) compared to a more extensive complete neck dissection have been reported, calling into question the routine use of a comprehensive neck dissection.…”
mentioning
confidence: 99%